SISTEM INFORMASI PENGELOLAAN DATA HASIL PRODUKSI PADA PT.PUTRA MANDIRI INTIPACK - Taufiki Ma'rufan; Nuril Lutvi Azizah; Ika Ratna Indra Astutik (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The development of the current era of globalization is very sophisticated. Therefore, information systems using computer technology will make it easier for us to manage data. In this case there are problems in the process of recording the production data management information system at PT. Putra Mandiri Intipack. using a manual or paper system which can result in errors in the management of production data. Therefore, to overcome these problems, a web-based production data management information system is needed. With this system, it can reduce errors in data storage and make it easier for the production department to input data. The purpose of this research is to build a production data management information system at PT. Putra Mandiri Intipack uses the codeigniter4 framework and uses the research and development (R&D) method and the results of the blackbox testing show that the production data management information system has all the features functioning as they should. Data from user testing observations with the highest presentation value of 64.7% and lowest 0.0%. The results of this study are in accordance with what is believed by PT. Putra Mandiri Intipack which includes management of data printing, lamination, slitting and sales. Data entry includes date, number, item name, amount and description. It is hoped that this system will make it easier for companies to manage production data and store data properly.